Penyuluhan dan Penanganan Dini Gangguan Jiwa di Lingkup Keluarga di Masyarakat Pesisir Baubau - Darfin Darfin; Julianto Julianto; Lukman Gani; Nashatun Nashatun (Universitas Muhammadiyah Manado, 2021)
Mental disorders are health issues that often go undetected in their early stages, especially in coastal communities with limited access to mental health services. Counseling and early intervention are strategic steps in preventing and managing mental disorders within families and communities. This study aims to analyze the effectiveness of mental health counseling programs and early intervention approaches in detecting and managing mental disorders in the coastal community of Baubau. The research employs a qualitative approach using in-depth interviews, participatory observation, and literature studies. Participants include families with members experiencing symptoms of mental disorders, healthcare workers, and community leaders involved in counseling programs. The results indicate that social stigma remains a major obstacle to early detection of mental disorders. Community-based counseling and approaches rooted in local wisdom have proven more effective in increasing awareness of mental health. Additionally, family involvement in care and social support from the surrounding environment play a crucial role in the recovery process of individuals with mental disorders. This study concludes that integrated counseling efforts within primary healthcare services, combined with strong social support, can improve early detection and treatment of mental disorders in coastal communities. Therefore, policies should focus on enhancing the capacity of healthcare workers and encouraging active community participation in supporting family mental health.